Investigation of corrosion performance of aluminum and zinc alloys in three acidic media. Issue 1 (12th January 2020) - Owoeye, Femi Timothy; Adetunji, Olayide R.; Omotosho, Adegbenro; Azodo, Adinife P.; Aiyedun, Peter O.
Abstract : The consequences of corrosion are many and varied, and their effects of these on the safe, reliable and efficient operation of equipment or structures are often more serious than a simple loss of metal mass. This research investigates the corrosion performance of two nonferrous metals in three acidic media, namely sulfuric acid (98% volume of H2 SO4 ), hydrochloric acid (75% volume of HCl), and trioxonitrate (V) acid (75% volume of HNO3 ). The corrosion rate is determined by the weight loss method, and the characterization of metallic samples is obtained by scanning electron microscope (SEM). The SEM shows the cracking pattern of grains indicating surface erosion due to the corrosion effects which are more depicted on the zinc than aluminum samples. It is shown that the solution of H2 SO4 has the highest impact on the corrosion rates of metallic samples, whereas the least effect is observed on the solution of HNO3 . It is observed that Zn alloy sample in 3 M H2 SO4 records the highest corrosion rate of 138.64 mm/year, while the aluminum alloy sample has the lowest rate of 24.661 mm/year after 72 hours of exposures in the acid. The corrosion rates of the samples decrease as the exposure time increases. The weight loss intensity increases with exposure time for Al samples and varies for Zn sample in acidic media. In conclusion, the higher the acid molarity, the shorter the exposure time and the higher the corrosion rates for both zinc and aluminum alloy samples. Abstract : It involved investigation of corrosion performance of two non ferrous metals in three different acidic media using weight loss method. The analysis was further determined microstructurally by using scanning electron microscope